PRODRUG AND RECEPTOR MEDIATED DRUG TARGETING STRATEGIES OF PROSTATE CANCER - NAVEEN G.,; SEETHA DEVI A., (International Journal of Pharma and Bio Sciences, 2015)
Prostate cancer is the most leading cause for death in elder male patients after lung cancer. It was age dependent and was not easily identified through symptoms due to its slow advancement from local small prostate tumors to highly metastasized prostate cells located in local lymph nodes and bones and most of patients die with the disease without prior detection. Negligence or identification in late stage lead to evolution of anti androgen therapy resistant cancer indicating the need of targeting of drug to both localized prostate cancer cells and metastasized cells. Prodrugs and receptor targeting agents can help in targeting specifically cancerous prostate cells by taking advantage of biological process that occur in cancer cells. They are reliable targeting agents which make therapeutic agents to be available at site of action for maximum potentiation of action and there is a need for progressive research in this field.